The Effect of Chlorella vulgaris Supplementation on Liver Enzymes, Serum Glucose and Lipid Profile in Patients with Non-Alcoholic Fatty Liver Disease - Mehrangiz Ebrahimi-Mameghani; Soodabeh Aliashrafi; Yousef Javadzadeh; Mohammad AsghariJafarabadi (Tabriz University of Medical Sciences, 2014)
Background: Non-alcoholic fatty liver disease (NAFLD) is becoming a public health problem worldwide and using microalgae is a new approach on its treatment. The aim of this study was to investigate the effect of Chlorella vulgaris supplementation on liver enzymes, serum glucose and lipid profile in patients with NAFLD. Methods: This double-blind randomized placebo-controlled clinical trial was conducted on 60 NAFLD patients from specialized clinics of Tabriz University of Medical Sciences from December 2011 to July 2012. The subjects were randomly allocated into 2 groups: 1) "intervention" (n=30) received 400 mg/day vitamin E plus four 300 mg tablets of Chlorella vulgaris and, 2) "placebo" (n=30) received 400 mg/day vitamin E and four placebo tablets per day for 8 weeks. Weight, liver enzymes and metabolic factors were assessed in fasting serum and dietary data was collected at baseline and end of the study. Results: Weight, liver enzymes, fasting blood sugar (FBS) and lipid profile decreased significantly in both groups (P<0.05). The differences in weight, ALP and FBS between the two groups were statistically significant (P=0.01, P=0.04 and P=0.02, respectively). Conclusion: C. vulgaris seems to improve FBS and lipid profile and therefore could be considered as an effective complementary treatment in NAFLD.